2018
DOI: 10.1519/jsc.0000000000002875
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Acceleration in English Premier League Academy Soccer Players

Abstract: Global thresholds are typically utilized to band acceleration dependent upon intensity. However, global thresholds do not account for variation in individual capacities, failing to quantify true intensity of acceleration. Previous research has investigated discrepancies in high-speed distance produced utilizing global and individual speed thresholds, not yet investigated for acceleration. The current aim was to investigate discrepancies between global and individual thresholds when quantifying acceleration tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…For instance, the study of Clemente et al [ 19 ] found small-to-moderate effect size differences for the number of sprints in acute load, TM and TS through different external load metrics. Moreover, the present study does not consider individual differences in acceleration and deceleration capacities, which can result in different results [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the study of Clemente et al [ 19 ] found small-to-moderate effect size differences for the number of sprints in acute load, TM and TS through different external load metrics. Moreover, the present study does not consider individual differences in acceleration and deceleration capacities, which can result in different results [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the knowledge about the overall running demands of training sessions and matches, it is important to understand intense periods and the actions that occur (i.e., sprints, repeated sprints, accelerations and decelerations), as they have a substantial influence on the biomechanical and cardiometabolic demands experienced by players. The evidence indicates that an increasingly greater number of accelerations and decelerations is performed at higher standards, and this needs to be a consideration when designing training plans [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individualized speed zones are based on a combination of maximal aerobic speed (MAS) which is derived from the Yo-yo intermittent recovery test level 1 or tested directly using another test, maximal sprint speed (MSS) which is derived from the maximal speed reached during training, and the anaerobic speed reserve (ASR) which corresponds to <80% of MAS, 80-100% of MAS, 100% of MAS, or 29% of ASR and ≥30% of ASR (Hunter et al, 2015;Rago et al, 2019a) (Table 1). For acceleration and deceleration zones, most studies used +3/−3 m•s −2 as threshold of intense/high acceleration or deceleration, respectively Abbott et al, 2018a;Malone et al, 2019;Rago et al, 2019b). However, recent studies (Delaney et al, 2017;Rago et al, 2019b) suggest that a maximum threshold of +2/−2 m•s −2 should be preferred over +3/−3 m•s −2 .…”
Section: Relevant Parameters From Global Positioning System Datamentioning
confidence: 99%
“…sn -2 ; DEC actions at -1-2, -2-3, and >-3 m . sn -2 , respectively (Abbott, Brickley, Smeeton, & Mills, 2018).…”
Section: Internal Training Loadmentioning
confidence: 99%